1994
DOI: 10.1080/00288233.1994.9513048
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium status of soils, plants, and grazing animals in New Zealand

Abstract: The accumulation of cadmium (Cd), a biotoxic heavy metal, in the food chain is undesirable. A national survey of soils and plants and random testing of kidneys from grazing animals slaughtered for export was conducted to assess Cd accumulation in New Zealand (NZ) pastoral agriculture. Average total Cd content of pastoral soils (0-7.5 cm) was 0.44 (Xg Cd/g compared to 0.20 |xg Cd/g for "native" (non-agricultural) soils. Total soil Cd was highly correlated to total soil P. An increase in total soil P is a reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 18 publications
2
51
1
1
Order By: Relevance
“…Most of the Cd that has entered the farming system in New Zealand has been introduced as a component of the fertiliser, superphosphate. Roberts et al (1994) reported a range of 0.04-1.53 mg Cd kg" 1 soil for New Zealand pastoral soils with a history of superphosphate topdressing. As a consequence of these findings and elevated Cd levels in meat products, rock phosphates with lower Cd content (Baechle & Wolstein 1984;Loganathan et al 1995) are now being used by the New Zealand fertiliser industry in an effort to minimise further contamination of farmland.…”
Section: Heavy Metal Contaminationmentioning
confidence: 99%
“…Most of the Cd that has entered the farming system in New Zealand has been introduced as a component of the fertiliser, superphosphate. Roberts et al (1994) reported a range of 0.04-1.53 mg Cd kg" 1 soil for New Zealand pastoral soils with a history of superphosphate topdressing. As a consequence of these findings and elevated Cd levels in meat products, rock phosphates with lower Cd content (Baechle & Wolstein 1984;Loganathan et al 1995) are now being used by the New Zealand fertiliser industry in an effort to minimise further contamination of farmland.…”
Section: Heavy Metal Contaminationmentioning
confidence: 99%
“…The objectives of this study were firstly to evaluate the effect of soil pH on plant uptake of Cd, using soils with low Cd concentrations that are typical in New 170 New Zealand Journal of Crop and Horticultural Science, 1999, Vol. 27 Zealand (0.04-1.53 |ig g 1 ) (Roberts et al 1994). In addition, the suitability of a number of commonly used soil extractants as predictors of Cd phytoavailability in soils with varying pHs was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd), a heavy metal potentially toxic to both humans and animals, is accumulating in many New Zealand and Australian pastoral soils mainly as a result of phosphate fertiliser use (Williams & David 1973;Merry 1988;Roberts et al 1994;Zanders 1999). Cadmium in pastoral soils has become an issue during the last 10 years because of its accumulation in offal products of grazing animals.…”
Section: Introductionmentioning
confidence: 99%